Random coincidence and angular correlation corrections in the sum-peak method using Monte Carlo simulations. (February 2021) - Nemeš, T.; Mrdja, D.; Bikit, I.
Abstract: The sum-peak method is a technique for measuring the absolute activity of gamma cascade emitting sources with a single gamma spectrometer. The effects of angular correlations and random coincidences, if not taken into account, can significantly reduce the accuracy of the method. However, we show that Monte Carlo simulations can reproduce the spectral data with a sufficient quality to perform the required corrections. In this work, we introduced a novel approach for data corrections for angular correlations and pile-up using Monte Carlo simulations. Furthermore, the new method for forming the count rate equations leads to a new formula for the sum-peak method, including random coincidences of any order. Highlights: A novel approach using Monte Carlo simulations is developed for spectral data corrections due to pile-up and the angular correlations. A new formula for the sum peak method including random coincidences of any order is deduced. The method is verified by the activity measurement of the 60 Co source.